Intracrater Sediment Trapping and Transport in Arabia Terra, Mars. Issue 9 (21st September 2020) - Dorn, Taylor; Day, Mackenzie
Abstract: Craters are the most prevalent basins and potential depocenters of sediment on Mars. Within these craters and extending from them, terminal dune fields and wind streaks are abundant, indicating active sediment transport and providing a way to study how wind and sediment interact with crater topography. Here we explore the role of craters as both sources and sinks in the modern Martian sedimentary cycle. Our results show that craters with low albedo wind streaks (indicative of sediment transport out of a crater and downwind dust removal) have lower crater wall slopes (9.4° ± 5.5°) compared to craters without wind streaks (17° ± 5.8°). We interpret that crater wall slopes play a dominant role in whether sediment is transported out of a crater basin and infer, from measurements of craters on Mars, that a crater transitions from being a net sediment sink to a net sediment source when crater wall slopes decrease to ~15°. This threshold value is consistent with limits of bedform climb observed on Earth and elsewhere on Mars. Plain Language Summary: Craters can collect sediment and are prevalent on Mars. Dune fields, within craters, and wind streaks, outside of craters, show that sediment is actively being transported and provide a way to study how wind and sediment interact with craters. Here we focus on craters that have interior dune fields to understand sediment being transported out of a crater. Our measurements of crater wall slopes show that the slope of the wall primarily determines whether sediment can escape from a crater. We conclude that craters transition from trapping sediment to losing sediment when crater wall slopes decrease to ~15°. Key Points: The slope of a crater wall plays a dominant role in sediment trapping by a crater Craters associated with low albedo wind streaks have lower crater wall slopes compared to craters without wind streaks A crater transitions from being a sink to a source of sediment when the crater wall slope is between 10° and 20°, most commonly at ~15°